DETERMINATION OF UJRAH ON MULTI-JASA FINANCING BTN iB PERSPECTIVE FATWA DSN MUI No. 44/DSN-MUI/VIII/2004: CASE STUDY OF BANK BTN KC SYARIAH MEDAN - Bambang Yulianto,; Suparmin, Sudirman (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2023)
The purpose of this research is to find out the practice of the basic kafalah bil ujrah contract on BTN iB multiservice financing occurring at BTN KC Syariah Medan and the low determination of ujrah is in accordance with DSN-MUI Fatwa No. 44/DSN-MUI/VII/2004 corcerning multiservice financing. This type of research is field research using a qualitative approach. Data was obtained using interview literature study, then analyzed using descriptive analysis methods. The results of this research show that: First, in practice the kafalah bil ujrah contract in multiservice financing at BTN KC Syariah Medan is harmonious and the conditions are met as in accordance with the provisions of Fatwa DSN-MUI No. 11/DSN/MUI/-/IV/2000 concerning kafalah. Second, the determination of ujrah on multiservice financing at BTN Syariah in the form of a percentage is carried out based on the Directors' Circular Letter (SED) issued by the head office of Bank Tabungan Negara (BTN) Syariah which is located in Jakarta, so that parties from the Syariah Branch Office do not have the right to change these provisions. However, in order to avoid ambiguity, BTN Syariah Medan also attached the ujrah in nominal form.